Light-curing sheet adhesive

By using epoxy resin with low glass transition temperature and photocationic polymerization initiator in the photocurable sheet adhesive, the problem of insufficient curing reaction under light irradiation is solved, and the photocurable sheet adhesive is realized. Fully curing and performance improvement.

CN115427526BActive Publication Date: 2025-02-25LINTEC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180026376.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-30
Filing Date
2021-03-26
Publication Date
2025-02-25
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

When the conventional photocurable sheet-like adhesive is irradiated only by light, the curing reaction cannot be carried out sufficiently, resulting in unreacted curable components remaining in the adhesive cured product, affecting its performance.

Method used

By using an epoxy resin that provides a cured product with a glass transition temperature (Tg) of 25°C or less, and combining a binder resin and a photocationic polymerization initiator, the photocurable sheet-like adhesive is realized by only light irradiation. It can be fully cured.

Benefits of technology

This method ensures sufficient curing of the photocurable sheet-like adhesive, avoids the problem of unfinished curing reaction, and improves the performance and stability of the cured substance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure DEST_PATH_IMAGE003
    Figure DEST_PATH_IMAGE003
Patent Text Reader

Abstract

The present invention provides a photocurable sheet adhesive, which is a photocurable sheet adhesive containing the following (A) components, (B) components and (C) components, wherein at least one of the epoxy resins constituting the (B) component is an epoxy resin that provides a cured product having a glass transition temperature (Tg) of 25° C. or less. The photocurable sheet adhesive can be fully cured only by light irradiation. (A) component: an adhesive resin component composed of one or more adhesive resins; (B) component: an epoxy-based curing component composed of one or more epoxy resins; (C) component: a photocationic polymerization initiator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a photocurable sheet-like adhesive that can be sufficiently cured only by light irradiation. Background Art

[0002] Conventionally, epoxy resins have been used as curable components of curable adhesives.

[0003] For example, Patent Document 1 describes a thermosetting sheet adhesive containing an epoxy resin, wherein a cured product of the thermosetting sheet adhesive satisfies specific requirements regarding storage modulus.

[0004] Generally, when a curable adhesive containing an epoxy resin is cured, a three-dimensional cross-linked structure is formed inside the cured adhesive. Therefore, in the curable adhesive containing an epoxy resin, the molecular motion of the curable component decreases during the curing reaction, and the curing reaction sometimes cannot be fully performed. If the curing reaction cannot be fully performed, the following problems may occur: the cured adhesive having the target properties cannot be obtained; or unreacted curable components remain in the cured adhesive, and the curable components are dissolved.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent document 1: Japanese Patent Application Publication No. 2017-110128. Summary of the invention

[0008] Problems to be solved by the invention

[0009] When a thermosetting sheet-shaped adhesive as described in Patent Document 1 is used, the curing reaction is generally initiated by heating, and the curing reaction proceeds directly under high temperature conditions, so that the molecular motion of the curable component can be kept active for a long time.

[0010] On the other hand, although the curing reaction of the photocurable sheet adhesive can be induced by light irradiation alone without heating, when the photocurable sheet adhesive is used, if only light irradiation treatment is performed without heating treatment, the above-mentioned problem caused by insufficient progress of the curing reaction is likely to occur.

[0011] An object of the present invention is to improve the curability of a photocurable sheet-shaped adhesive. That is, an object of the present invention is to provide a photocurable sheet-shaped adhesive that can be sufficiently cured only by light irradiation without heat treatment.

[0012] Means for solving problems

[0013] In order to solve the above problems, the present inventors have conducted intensive research on photocurable sheet adhesives containing epoxy resins. As a result, it has been found that by using an epoxy resin that provides a cured product with a glass transition temperature (Tg) of 25° C. or less, a photocurable sheet adhesive that can be fully cured by light irradiation alone can be obtained, thereby completing the present invention.

[0014] That is, according to the present invention, the photocurable sheet-like adhesives described in the following [1] to [8] are provided.

[0015] [1] A photocurable sheet adhesive comprising the following components (A), (B) and (C), wherein at least one epoxy resin constituting the component (B) is an epoxy resin [epoxy resin (BL)] that provides a cured product having a glass transition temperature (Tg) of 25° C. or less,

[0016] (A) component: a binder resin component composed of one or more binder resins;

[0017] (B) component: an epoxy curable component composed of one or more epoxy resins;

[0018] (C) Component: photocationic polymerization initiator.

[0019] [2] The photocurable sheet-like adhesive according to [1], wherein at least one of the binder resins constituting the component (A) is a phenoxy resin.

[0020] [3] The photocurable sheet-like adhesive according to [1] or [2], wherein at least one type of binder resin constituting the component (A) is a polyvinyl acetal resin.

[0021] [4] The photocurable sheet-like adhesive according to any one of [1] to [3], wherein the content of the component (B) is 35 to 75% by mass based on the total mass of the photocurable sheet-like adhesive.

[0022] [5] The photocurable sheet-like adhesive according to any one of [1] to [4], wherein the epoxy resin (BL) is an epoxy resin having an oxyalkylene structure.

[0023] [6] The photocurable sheet-like adhesive according to any one of [1] to [5], wherein at least one of the epoxy resins constituting the component (B) is liquid at 23°C.

[0024] [7] The photocurable sheet adhesive according to any one of [1] to [6], wherein the storage shear modulus (G'0) at 0°C and the storage shear modulus (G'0) at 100°C of a cured product obtained by curing the photocurable sheet adhesive using a high pressure mercury lamp under the following conditions are:100 ), the following formula (I) is fully satisfied:

[0025] [Mathematical formula 1]

[0026]

[0027] [Curing conditions of photocurable sheet adhesive]

[0028] Temperature: 23℃;

[0029] Illuminance when measured at a wavelength of 365 nm: 200 mW / cm 2 ;

[0030] The total amount of light measured at a wavelength of 365 nm is 1000 mJ / cm 2 .

[0031] [8] The photocurable sheet-like adhesive according to any one of [1] to [7], which is used for producing an optical device.

[0032] Effects of the Invention

[0033] According to the present invention, there is provided a photocurable sheet-shaped adhesive which can be sufficiently cured only by light irradiation without heat treatment. DETAILED DESCRIPTION

[0034] The photocurable sheet adhesive of the present invention is a photocurable sheet adhesive containing the above-mentioned components (A), (B) and (C), wherein at least one of the epoxy resins constituting the component (B) is an epoxy resin that provides a cured product having a glass transition temperature (Tg) of 25° C. or less.

[0035] The sheet-shaped adhesive refers to an adhesive that is non-fluid at room temperature (23° C., the same below) and is formed into a sheet. In the present invention, the photocurable sheet-shaped adhesive may be in a short strip or a long strip (tape).

[0036] In this specification, a "photocurable sheet-like adhesive" may be described as a "sheet-like adhesive".

[0037] [(A) ingredient]

[0038] The photocurable sheet-like adhesive of the present invention contains a binder resin component composed of one or more binder resins as the component (A). The component (A) consists only of the binder resin.

[0039] In the present invention, the “binder resin component” refers to a binder resin when the photocurable sheet-like adhesive contains one binder resin, and refers to a mixture of two or more binder resins when the photocurable sheet-like adhesive contains two or more binder resins.

[0040] The “binder resin” refers to a polymer component that imparts shape retention or flexibility to the photocurable sheet-like adhesive.

[0041] The photocurable sheet-like adhesive of the present invention easily maintains a certain shape even in an uncured state by containing the component (A).

[0042] The content of the component (A) is preferably 20 to 60% by mass, more preferably 25 to 53% by mass, and even more preferably 30 to 45% by mass, based on the entire photocurable sheet-like adhesive.

[0043] By setting the content of the component (A) in the above range, a photocurable sheet-like adhesive having sufficient shape retaining properties can be easily obtained.

[0044] The weight average molecular weight (Mw) of the binder resin constituting the component (A) is preferably 10,000 to 300,000, more preferably 30,000 to 200,000.

[0045] The weight average molecular weight (Mw) of the binder resin can be determined as a standard polystyrene-equivalent value by performing gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a solvent.

[0046] As the binder resin, a binder resin having a glass transition temperature (Tg) of 50° C. or higher is preferred, and a binder resin having a glass transition temperature (Tg) of 80° C. or higher is more preferred.

[0047] When the content of the component (B) is increased, the shape retainability of the photocurable sheet-shaped adhesive may be reduced. However, by containing a binder resin having a glass transition temperature (Tg) of 50° C. or higher, this problem is less likely to occur.

[0048] The upper limit of the glass transition temperature (Tg) of the binder resin is not particularly limited, but is usually 200° C. or lower.

[0049] The glass transition temperature (Tg) of the binder resin can be measured in accordance with JIS K 7121 using a differential scanning calorimeter.

[0050] Examples of the binder resin include olefin resins, acrylic polymers, polyester resins, polyvinyl alcohol resins, polyvinyl acetal resins, polyvinyl chloride, phenoxy resins, polyamide resins, cellulose materials, polyvinyl ethers, polyimide resins, styrene-isoprene-styrene block copolymers, and styrene-butadiene-styrene block copolymers.

[0051] The binder resins may be used alone or in combination of two or more.

[0052] At least one of the binder resins is preferably a phenoxy resin.

[0053] Phenoxy resin is a polymer with a main chain of an addition polymerization structure of an aromatic diol and an aromatic diglycidyl ether. Phenoxy resin is generally equivalent to a high molecular weight epoxy resin and refers to a phenoxy resin with a polymerization degree of about 100 or more.

[0054] Among the phenoxy resins, there are phenoxy resins having a high glass transition temperature (Tg), and such phenoxy resins are suitable for use as a binder resin.

[0055] The epoxy equivalent of the phenoxy resin is preferably 5,000 g / eq or more, more preferably 7,000 g / eq or more. The value of the epoxy equivalent can be measured in accordance with JIS K 7236 (the same applies hereinafter).

[0056] Examples of the phenoxy resin include bisphenol A type phenoxy resin, bisphenol F type phenoxy resin, bisphenol S type phenoxy resin, bisphenol A type and bisphenol F type copolymer type phenoxy resin, bisphenol E type phenoxy resin, naphthalene type phenoxy resin, novolac type phenoxy resin, biphenyl type phenoxy resin, and cyclopentadiene type phenoxy resin.

[0057] These phenoxy resins can be used alone or in combination of two or more.

[0058] The phenoxy resin can be obtained by a method of reacting a difunctional phenol with an epihalohydrin to obtain a high molecular weight or by a method of subjecting a difunctional epoxy resin to an addition polymerization reaction with a difunctional phenol.

[0059] For example, a phenoxy resin can be obtained by reacting a difunctional phenol with an epihalohydrin in the presence of an alkali metal hydroxide in an inert solvent at a temperature of 40 to 120° C. Alternatively, a difunctional epoxy resin and a difunctional phenol can be reacted in the presence of a catalyst such as an alkali metal compound, an organic phosphorus compound, a cyclic amine compound, in an organic solvent such as an amide solvent, an ether solvent, a ketone solvent, a lactone solvent, an alcohol solvent, etc. having a boiling point of 120° C. or more, at a reaction solid content concentration of 50% by weight or less, and heated to 50 to 200° C. to carry out a polyaddition reaction to obtain a phenoxy resin.

[0060] The difunctional phenols are not particularly limited as long as they are compounds having two phenolic hydroxyl groups. Examples include: monocyclic difunctional phenols such as hydroquinone, 2-bromohydroquinone, resorcinol, and catechol; bisphenols such as bisphenol A, bisphenol F, bisphenol AD, and bisphenol S; dihydroxybiphenyls such as 4,4'-dihydroxybiphenyl; dihydroxyphenyl ethers such as bis(4-hydroxyphenyl)ether; and compounds obtained by introducing straight-chain alkyl groups, branched-chain alkyl groups, aryl groups, hydroxymethyl groups, allyl groups, cyclic aliphatic groups, halogens (tetrabromobisphenol A, etc.), nitro groups, etc. into the aromatic rings of these phenol skeletons; and polycyclic difunctional phenols obtained by introducing straight-chain alkyl groups, branched-chain alkyl groups, allyl groups, substituted allyl groups, cyclic aliphatic groups, alkoxycarbonyl groups, etc. into the carbon atoms located in the center of these bisphenol skeletons.

[0061] Examples of the epihalohydrin include epichlorohydrin, epibromohydrin, epiiodohydrin, and the like.

[0062] In the present invention, commercially available phenoxy resins may be used, for example, YX7200 (glass transition temperature (Tg): 150°C), YX6954 (phenoxy resin containing a bisphenol acetophenone skeleton, glass transition temperature (Tg): 130°C), and YP70 (glass transition temperature (Tg): 70°C) manufactured by Mitsubishi Chemical Corporation.

[0063] At least one of the binder resins is preferably a polyvinyl acetal resin.

[0064] The polyvinyl acetal resin is a polymer obtained by an acetalization reaction between a hydroxyl group of polyvinyl alcohol (or a partially saponified product of its ester, the same below) and an aldehyde.

[0065] In order to obtain a photocurable sheet adhesive that provides a cured product with better bonding strength, the photocurable sheet adhesive preferably contains a large amount of curable component (component (B)). However, a photocurable sheet adhesive containing a large amount of component (B) tends to have a reduced uniformity of the components, and as a result, the transparency of the obtained cured product may be reduced.

[0066] By using a polyvinyl acetal resin as a binder resin, the uniformity of the components can be improved, and a photocurable sheet-like adhesive that provides a cured product having excellent transparency can be easily obtained.

[0067] When a phenoxy resin is used as the binder resin, the uniformity of the components may be reduced. However, when the component (A) contains both a phenoxy resin and a polyvinyl acetal resin, the uniformity of the components of the photocurable sheet adhesive becomes good.

[0068] Examples of the polyvinyl acetal resin include polyvinyl butyral obtained by reacting polyvinyl alcohol with butyraldehyde, polyvinyl formal obtained by reacting polyvinyl alcohol with formaldehyde, and polyvinyl acetal obtained by reacting polyvinyl alcohol with acetaldehyde.

[0069] These polyvinyl acetal resins can be used alone or in combination of two or more.

[0070] The polyvinyl acetal resin can be synthesized by reacting polyvinyl alcohol with aldehyde using an acid catalyst in an appropriate solvent. Examples of the solvent used include water; alcohol solvents such as methanol and ethanol; mixed solvents consisting of water and alcohol; and aprotic polar solvents such as dimethyl sulfoxide.

[0071] Alternatively, the polyvinyl acetal resin can be synthesized by adding an acid catalyst and an aldehyde to a polyvinyl acetate solution and reacting the mixture.

[0072] The acid catalyst used is not particularly limited, and examples thereof include organic acids such as acetic acid and p-toluenesulfonic acid; and inorganic acids such as nitric acid, sulfuric acid, and hydrochloric acid.

[0073] [(B) ingredient]

[0074] The photocurable sheet-like adhesive of the present invention contains an epoxy curable component composed of one or more epoxy resins as the component (B). The component (B) consists only of the epoxy resin.

[0075] In the present invention, the “epoxy-based curable component” refers to a single epoxy resin when the photocurable sheet-like adhesive contains the epoxy resin, and refers to a mixture of two or more epoxy resins when the photocurable sheet-like adhesive contains the epoxy resins.

[0076] In addition, even if it is a compound which has an epoxy group, the compound corresponding to the binder resin which comprises (A) component is regarded as not constituting (B) component.

[0077] The photocurable sheet-like adhesive of the present invention functions as a curable sheet-like adhesive by containing the component (B).

[0078] The content of the component (B) is preferably 35 to 75% by mass, more preferably 45 to 70% by mass, and even more preferably 53 to 65% by mass, based on the entire photocurable sheet-like adhesive.

[0079] When the content of the component (B) is within the above range, a photocurable sheet-like adhesive having sufficient curability can be easily obtained.

[0080] The weight average molecular weight (Mw) of the epoxy resin constituting the component (B) is preferably 100 to 5,000, more preferably 200 to 4,000.

[0081] The weight average molecular weight (Mw) of the epoxy resin can be determined as a standard polystyrene-equivalent value by gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a solvent.

[0082] The epoxy equivalent of the epoxy resin is preferably 100 g / eq or more and 500 g / eq or less, and more preferably 115 g / eq or more and 450 g / eq or less. By curing the photocurable sheet adhesive containing the epoxy resin having an epoxy equivalent of 100 g / eq or more and 500 g / eq or less, a cured product having excellent bonding strength can be obtained.

[0083] Examples of the epoxy resin include monofunctional epoxy resins and polyfunctional epoxy resins.

[0084] From the viewpoint of easily obtaining a cured product having a higher adhesive strength, the epoxy resin is preferably a multifunctional epoxy resin.

[0085] The "polyfunctional epoxy resin" refers to an epoxy resin having two or more epoxy groups in the molecule.

[0086] Examples of the polyfunctional epoxy resin include aliphatic epoxy compounds (excluding alicyclic epoxy compounds), aromatic epoxy compounds, and alicyclic epoxy compounds.

[0087] Examples of the aliphatic epoxy compound include 1,4-butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, triglycidyl ether of glycerol, triglycidyl ether of trimethylolpropane, tetraglycidyl ether of sorbitol, hexaglycidyl ether of dipentaerythritol, diglycidyl ether of polyethylene glycol, and diglycidyl ether of polypropylene glycol.

[0088] Examples of the aromatic epoxy compound include: glycidyl ethers of bisphenol A, bisphenol F, or compounds obtained by further adding alkylene oxide thereto, or epoxy novolac resins; polyglycidyl ethers of aromatic compounds having two or more phenolic hydroxyl groups, such as resorcinol, hydroquinone, and catechol; glycidyl ethers of aromatic compounds having two or more alcoholic hydroxyl groups, such as phenyl dimethanol, phenyl diethanol, and phenyl dibutyl alcohol; glycidyl esters of polyacid aromatic compounds having two or more carboxylic acids, such as phthalic acid, terephthalic acid, and trimellitic acid; and the like.

[0089] Examples of the alicyclic epoxy compound include polyglycidyl ethers of polyols having at least one alicyclic structure, such as dicyclopentadienyl dimethanol diglycidyl ether and hydrogenated products of bisphenol A, and cycloalkene oxide compounds such as cyclohexene oxide or cyclopentene oxide-containing compounds obtained by epoxidizing a cyclohexene or cyclopentene ring-containing compound using an oxidizing agent.

[0090] The epoxy resins can be used alone or in combination of two or more.

[0091] At least one epoxy resin constituting the component (B) is an epoxy resin [epoxy resin (BL)] that provides a cured product having a glass transition temperature (Tg) of 25° C. or less.

[0092] The glass transition temperature (Tg) of the cured product of the epoxy resin can be determined by differential scanning calorimetry.

[0093] "Epoxy resin that provides a cured product with a glass transition temperature (Tg) of 25°C or less" refers to an epoxy resin that provides a cured product with a glass transition temperature (Tg) of 25°C or less when cured alone or in the presence of a curing agent or the like. The conditions for forming the cured product are not particularly limited as long as a sufficiently cured cured product can be obtained. For example, as described in the Examples, a cured product for measurement can be obtained using a thermal cationic polymerization initiator.

[0094] The epoxy resin (BL) has sufficient molecular mobility even when the curing reaction proceeds and constitutes a part of the cured product. Therefore, by using the component (B) containing the epoxy resin (BL), a photocurable sheet adhesive can be obtained that can be fully cured by light irradiation alone even without heat treatment. From the perspective of making this effect more significant, the epoxy resin (BL) is preferably an epoxy resin that provides a cured product with a glass transition temperature (Tg) of less than -5°C, and more preferably an epoxy resin that provides a cured product with a glass transition temperature (Tg) of less than -20°C.

[0095] Examples of the epoxy resin (BL) include epoxy resins having an oxyalkylene structure. Since epoxy resins having an oxyalkylene structure tend to provide cured products having relatively low glass transition temperatures (Tg), they are preferably used as the epoxy resin (BL).

[0096] Examples of the oxyalkylene structure include methylene oxide, ethylene oxide, propylene oxide, trimethylene oxide, butenyl oxide, pentenyl oxide, hexenyl oxide, heptenyl oxide, octenyl oxide, nonenyl oxide, decenyl oxide, undecenyl oxide, dodecenyl oxide, tridecenyl oxide, tetradecenyl oxide, pentadecenyl oxide, cyclopropenyl oxide, cyclobutenyl oxide, cyclopentenyl oxide, cyclohexenyl oxide, decahydronaphthylidene oxide, norbornyl oxide, and adamantyl oxide.

[0097] The content of the epoxy resin (BL) constituting the component (B) (when there are two or more epoxy resins (BL), the total amount thereof) is usually 80 to 100% by mass, preferably 90 to 100% by mass, and more preferably 95 to 100% by mass, relative to the entire component (B).

[0098] By setting the content of the epoxy resin (BL) to 80% by mass or more based on the entirety of the component (B), a photocurable sheet-shaped adhesive that can be sufficiently cured simply by light irradiation can be easily obtained.

[0099] The content of the epoxy resin (BL) is preferably 35 to 75% by mass, more preferably 37 to 70% by mass, and even more preferably 40 to 65% by mass, based on the entire photocurable sheet-like adhesive.

[0100] It is preferred that at least one epoxy resin constituting the component (B) is liquid at 23°C.

[0101] “Liquid at 23° C.” means having fluidity at 23° C. The epoxy resin preferably has a viscosity of 2 to 10,000 mPa·s as measured at 23° C. and 1.0 rpm using an E-type viscometer.

[0102] By using an epoxy resin that is liquid at 23°C, a photocurable sheet adhesive having a low elastic modulus at room temperature can be obtained. Since such a photocurable sheet adhesive has excellent adhesion at room temperature or mild high temperature conditions, the operation of heating and softening the photocurable sheet adhesive can be omitted in the pasting process; or pasting can be performed under relatively mild conditions of about 35 to 70°C.

[0103] When the photocurable sheet adhesive of the present invention contains an epoxy resin that is liquid at 23° C., the content of the epoxy resin that is liquid at 23° C. is preferably 35 to 75% by mass, more preferably 37 to 70% by mass, and even more preferably 40 to 65% by mass based on the entire photocurable sheet adhesive.

[0104] When the content of the epoxy resin (B) which is liquid at 23° C. is within the above range, a photocurable sheet-shaped adhesive having excellent adhesion at room temperature can be easily obtained.

[0105] The epoxy resin (BL) is preferably liquid at 23°C from the viewpoint of improving the curability and adhesion of the photocurable sheet-like adhesive.

[0106] [(C) ingredient]

[0107] The photocurable sheet-like adhesive of the present invention contains a photocationic polymerization initiator as the component (C).

[0108] The photocationic polymerization initiator is preferred because it can efficiently advance the polymerization reaction of the component (B) and can improve the storage stability of the photocurable sheet-like adhesive compared to other curing agents.

[0109] The photocationic polymerization initiator is a compound that generates cationic species by irradiation with ultraviolet rays to initiate a curing reaction of a cation-curable compound, and includes a cationic portion that absorbs ultraviolet rays and an anionic portion that serves as a source of acid generation.

[0110] Examples of the photocationic polymerization initiator include sulfonium salt compounds, iodonium salt compounds, phosphonium salt compounds, ammonium salt compounds, diazonium salt compounds, selenium salt compounds, oxonium salt compounds, and bromine salt compounds. Among these, sulfonium salt compounds are preferred from the perspective of excellent compatibility with other components, and aromatic sulfonium salt compounds having an aromatic group are more preferred.

[0111] Examples of the sulfonium salt compounds include triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, 4,4'-bis[diphenylsulfonium]diphenyl sulfide-bishexafluorophosphate, 4,4'-bis[di( β -hydroxyethoxy)phenylsulfonium] diphenyl sulfide-bis(hexafluoroantimonate), 7-[di(p-toluoyl)sulfonium]-2-isopropylthioxanthone hexafluorophosphate, 7-[di(p-toluoyl)sulfonium]-2-isopropylthioxanthone hexafluoroantimonate, 7-[di(p-toluoyl)sulfonium]-2-isopropyltetrakis(pentafluorophenyl)borate, phenylcarbonyl-4'-diphenylsulfonium-diphenyl sulfide-hexafluorophosphate, phenylcarbonyl-4'-diphenylsulfonium-diphenyl sulfide-hexafluoroantimonate, 4-tert-butylphenylcarbonyl-4'-diphenyl Sulfonium-diphenyl sulfide-hexafluorophosphate, 4-tert-butylphenylcarbonyl-4'-diphenylsulfonium-diphenyl sulfide-hexafluoroantimonate, 4-tert-butylphenylcarbonyl-4'-diphenylsulfonium-diphenyl sulfide-tetrakis(pentafluorophenyl)borate, 4-(phenylthio)phenyldiphenylsulfonium hexafluoroantimonate, 4-(phenylthio)phenyldiphenylsulfonium hexafluorophosphate, 4-{4-(2-chlorobenzoyl)phenylthio}phenylbis(4-fluorophenyl)sulfonium hexafluoroantimonate, halides of phenylthiodiphenylsulfonium hexafluoroantimonate, 4,4',4''-tris( β 4-(phenylthio)phenyl)sulfonium hexafluoroantimonate, 4,4'-bis[diphenylsulfonium]diphenyl sulfide-bishexafluoroantimonate, diphenyl[4-(phenylthio)phenyl]sulfonium trifluorotris(pentafluoroethyl)phosphate, tris[4-(4-acetylphenylsulfanyl)phenyl]sulfonium tris[(trifluoromethyl)sulfonyl]methanide, a salt in which the cation part is 4-(phenylthio)phenyldiphenylsulfonium and the anion part is a phosphorus anion to which fluorine and perfluoroalkyl groups are added, and the like.

[0112] Examples of the iodonium salt compound include diphenyliodonium tetrakis(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, di(4-nonylphenyl)iodonium hexafluorophosphate, and (triisopropylphenyl)iodonium tetrakis(pentafluorophenyl)borate.

[0113] Examples of the phosphonium salt compound include tri-n-butyl(2,5-dihydroxyphenyl)phosphonium bromide and hexadecyltributylphosphonium chloride.

[0114] Examples of the ammonium salt compound include benzyltrimethylammonium chloride, phenyltributylammonium chloride, and benzyltrimethylammonium bromide.

[0115] The photocationic polymerization initiator can be used alone or in combination of two or more.

[0116] When the photocurable sheet-like adhesive contains a photocationic polymerization initiator, the content of the photocationic polymerization initiator is preferably 0.1 to 5% by mass, and more preferably 0.5 to 4% by mass, based on the entire photocurable sheet-like adhesive.

[0117] [Other ingredients]

[0118] The photocurable sheet-like adhesive of the present invention may contain other components within a range not impairing the effects of the present invention.

[0119] Examples of other components include additives such as a silane coupling agent, an ultraviolet absorber, an antistatic agent, a light stabilizer, an antioxidant, a resin stabilizer, a filler, a pigment, an extender, and a softener.

[0120] These can be used alone or in combination of two or more.

[0121] When the sheet-like adhesive of the present invention contains these additives, the content thereof can be appropriately determined depending on the purpose.

[0122] [Layer Structure of Photocurable Sheet-Shaped Adhesive]

[0123] The thickness of the photocurable sheet-like adhesive of the present invention is usually 1 to 50 μm, preferably 1 to 40 μm, and more preferably 2 to 30 μm.

[0124] The thickness of the photocurable sheet adhesive can be measured using a known thickness meter in accordance with JIS K 7130 (1999). When the photocurable sheet adhesive has a release film described below, the thickness of the photocurable sheet adhesive does not include the thickness of the release film.

[0125] From the viewpoint of protection from the external environment, the photocurable sheet-like adhesive of the present invention preferably has a release film on at least one surface, and may have release films on both surfaces.

[0126] It should be noted that the photocurable sheet adhesive of the present invention having a release film on at least one side is a state before use, and when using the photocurable sheet adhesive of the present invention, the release film is usually peeled off and removed. In the case where the photocurable sheet adhesive has release films on both sides, the release film with the lower release force is usually peeled off first.

[0127] As the release film, a resin film is generally used.

[0128] Examples of the resin component of the resin film include polyimide, polyamide, polyamideimide, polyphenylene ether, polyether ketone, polyether ether ketone, polyolefin, polyester, polycarbonate, polysulfone, polyether sulfone, polyphenylene sulfide, polyarylate, acrylic resin, cycloolefin polymer, aromatic polymer, polyurethane polymer, etc. Among these, polyester resin is preferred.

[0129] When the release film has a release agent layer, examples of the release agent include rubber elastomers such as silicone resins, olefin resins, isoprene resins, and butadiene resins, long-chain alkyl resins, alkyd resins, and fluorine resins.

[0130] The thickness of the release film is usually 10 to 300 μm, preferably 10 to 200 μm, and more preferably 15 to 100 μm.

[0131] [Method for producing photocurable sheet-like adhesive]

[0132] The method for producing the photocurable sheet-like adhesive of the present invention is not particularly limited, but can be produced by, for example, a casting method.

[0133] In the method of producing a photocurable sheet-shaped adhesive by a casting method, a photocurable sheet-shaped adhesive with a release film can be obtained by applying an adhesive composition as a raw material on a release film by a known method and drying the obtained coating film.

[0134] The adhesive composition contains the above-mentioned (A) component, (B) component, and (C) component, and other components as necessary.

[0135] The adhesive composition may further contain a solvent.

[0136] Examples of the solvent include aromatic hydrocarbon solvents such as benzene and toluene; ester solvents such as ethyl acetate and butyl acetate; ketone solvents such as acetone, methyl ethyl ketone and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as n-pentane, n-hexane and n-heptane; alicyclic hydrocarbon solvents such as cyclopentane, cyclohexane and methylcyclohexane, etc.

[0137] These solvents can be used alone or in combination of two or more.

[0138] When the adhesive composition contains a solvent, the content of the solvent can be appropriately determined in consideration of coating properties and the like.

[0139] The adhesive composition can be prepared by appropriately mixing and stirring the components according to a conventional method.

[0140] The release film for producing the photocurable sheet adhesive functions as a support in the production process of the photocurable sheet adhesive, and also functions as a release film of the photocurable sheet adhesive before the photocurable sheet adhesive is used.

[0141] Examples of a method for applying the adhesive composition include spin coating, spray coating, bar coating, knife coating, roll coating, doctor blade coating, die coating, and gravure coating.

[0142] Examples of a method for drying the coating film of the adhesive composition include conventionally known drying methods such as hot air drying, hot roll drying, and infrared irradiation.

[0143] The conditions for drying the coating film are, for example, 80 to 150° C. for 30 seconds to 5 minutes.

[0144] [Characteristics of photocurable sheet adhesive]

[0145] When curing the photocurable sheet-like adhesive of the present invention, ultraviolet rays are usually irradiated.

[0146] Specific examples of ultraviolet light sources include ultrahigh pressure mercury lamps, high pressure mercury lamps, low pressure mercury lamps, carbon arc lamps, black light fluorescent lamps, metal halide lamps, etc. In addition, as the wavelength of ultraviolet light to be irradiated, a wavelength range of 190 to 380 nm can be used.

[0147] The type of ultraviolet rays, the irradiation amount, the irradiation time, etc. can be appropriately determined according to the components of the sheet-like adhesive to be irradiated or the content of each component.

[0148] The irradiation intensity is preferably 20 to 1000 mW / cm 2 The light intensity is preferably 50 to 3000 mJ / cm 2 about.

[0149] The photocurable sheet-shaped adhesive of the present invention was cured using a high pressure mercury lamp under the following conditions to obtain a cured product, and the storage shear modulus (G'0) at 0°C and the storage shear modulus (G' 100 ), preferably fully satisfying the following formula (I):

[0150] [Mathematical formula 2]

[0151]

[0152] [Curing conditions of photocurable sheet adhesive]

[0153] Temperature: 23℃;

[0154] Illuminance when measured at a wavelength of 365 nm: 200 mW / cm2 ;

[0155] The total amount of light measured at a wavelength of 365 nm is 1000 mJ / cm 2 .

[0156] Generally, the storage modulus of a cured product is high under low temperature conditions and low under high temperature conditions. In addition, in a cured product in which a curable adhesive is fully cured and contains almost no unreacted curable components, the difference between the measured value under low temperature conditions and the measured value under high temperature conditions tends to be smaller. On the other hand, in a cured product in which the curable adhesive is not sufficiently cured and contains a large amount of unreacted curable components, there is a tendency to fluidize under high temperature conditions (i.e., the value of the storage modulus tends to be significantly reduced), and the difference between the measured value under low temperature conditions and the measured value under high temperature conditions tends to be larger.

[0157] Therefore, according to (G'0 / G' 100 ) value can be used to determine whether a three-dimensional cross-linked structure is sufficiently formed in the cured product (whether the curing reaction proceeds sufficiently).

[0158] For example, since the photocurable sheet adhesive of the present invention contains an epoxy resin (BL) as at least one of the components (B), the curing reaction can be sufficiently carried out by light irradiation alone without heat treatment. 100 The value of G'0 / G' is usually less than 100, preferably less than 50, and more preferably less than 15. 100 The lower limit of the value of is not particularly limited, but is usually greater than 1.0.

[0159] The above G'0 value is preferably 50 MPa or less, more preferably 15 MPa or less. A photocurable sheet adhesive having a G'0 value of 50 MPa or less is suitable for use as an adhesive for flexible devices. The lower limit of G'0 is not particularly limited, but is usually 0.1 MPa or more.

[0160] The above G' 100 The value of G' is preferably 0.1 MPa or more, more preferably 0.2 MPa or more. 100 The photocurable sheet adhesive having a G' value of 0.1 MPa or more is suitable as an adhesive for devices requiring heat resistance. 100 The upper limit of is not particularly limited, but is usually less than 50 MPa.

[0161] As described above, the photocurable sheet-like adhesive of the present invention can be sufficiently cured only by light irradiation.

[0162] Therefore, by using the photocurable sheet-like adhesive of the present invention as a material for forming adhesive members in various devices, it is possible to suppress the generation of defective products due to application of heat load or the generation of defective products due to insufficient progress of the curing reaction.

[0163] [Applications of photocurable sheet adhesives]

[0164] The photocurable sheet-like adhesive of the present invention is suitably used in the production of optical devices including a light-emitting element, a light-receiving element, a display element, and the like.

[0165] Examples of the optical device include an organic EL display, an organic EL lighting, a liquid crystal display, a solar cell, and electronic paper. Example

[0166] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited to the following Examples.

[0167] [Compounds used in Examples or Comparative Examples]

[0168] ・Binder resin (A1): phenoxy resin [manufactured by Mitsubishi Chemical Corporation, trade name: YX7200B35, glass transition temperature (Tg): 150°C, Mw: 30,000];

[0169] ・Binder resin (A2): polyvinyl acetal resin [manufactured by Sekisui Chemical Co., Ltd., trade name: S-LECKS-5Z, glass transition temperature (Tg): 113°C, Mw: 130,000];

[0170] ・Binder resin (A3): polyvinyl acetal resin [manufactured by Sekisui Chemical Co., Ltd., trade name: S-LECBX-25Z, glass transition temperature (Tg): 86°C, degree of polymerization: 2,300];

[0171] ・Binder resin (A4): phenoxy resin [manufactured by NIPPON STEEL Chemical & Material Co., Ltd., trade name: YP70, glass transition temperature (Tg): 70°C, Mw: 55,000];

[0172] ・Binder resin (A5): phenoxy resin [manufactured by Mitsubishi Chemical Corporation, trade name: YX7180BH40, glass transition temperature (Tg): 15°C, Mw: 40,000];

[0173] ・Epoxy resin (BL1): epoxy resin having an oxyalkylene group (liquid at 23°C) [manufactured by Mitsubishi Chemical Corporation, trade name: YX7400, epoxy equivalent: 440 g / eq, glass transition temperature (Tg) of cured product: -69°C];

[0174] ・Epoxy resin (BL2): epoxy resin having an oxyalkylene group (liquid at 23°C) [manufactured by ADEKA, trade name: ED-506, epoxy equivalent: 300 g / eq, glass transition temperature (Tg) of cured product: -50.7°C];

[0175] ・Epoxy resin (B1): hydrogenated bisphenol A type epoxy resin (liquid at 23°C) [manufactured by Mitsubishi Chemical Corporation, trade name: YX8000, epoxy equivalent: 205 g / eq, glass transition temperature (Tg) of cured product: 96.4°C];

[0176] ・Epoxy resin (B2): epoxy resin (liquid at 23°C) [manufactured by Daicel, trade name: Celloxide 2021P, epoxy equivalent: 128 to 145 g / eq, glass transition temperature (Tg) of cured product: 94.5°C];

[0177] ・Cationic polymerization initiator (C1): a photocationic polymerization initiator, 4-(phenylthio)phenyldiphenylsulfonium hexafluorophosphate [manufactured by San-Apro, trade name: CPI-100P].

[0178] In addition, the glass transition temperature (Tg) of the cured product of the epoxy resin constituting the (B) component is measured by the following method.

[0179] (Preparation of Measurement Samples)

[0180] 0.5 parts by mass of a thermal cationic polymerization initiator [manufactured by Sanshin Chemical Industry Co., Ltd., trade name: SI-B3A] was added to 100 parts by mass of each epoxy resin. The resulting mixture was poured into a polytetrafluoroethylene mold having a thickness of 1 mm and a size of 20 mm x 20 mm, and cured by heating at 100°C for 60 minutes to obtain a cured product (measurement sample).

[0181] (Differential Scanning Calorimetry)

[0182] The glass transition temperature was determined by performing differential scanning calorimetry using a differential scanning calorimeter [manufactured by TA Instrument, product name: DSCQ2000] according to the following method.

[0183] Specifically, the above-mentioned measurement sample was crushed, 5 mg was taken, put into an aluminum pan, sealed with a lid, kept at 120°C for 5 minutes, cooled, and then measured from -100°C to +120°C at a heating rate of 10°C / min.

[0184] The temperature at the intersection of a straight line extending from the base line on the low temperature side of the obtained curve toward the high temperature side and a tangent line drawn at a point where the gradient of the curve in the step-like change portion of the glass transition is maximum is taken as the glass transition temperature (Tg).

[0185] [Example 1]

[0186] 100 parts by mass of a binder resin (A1) (calculated as the active ingredient excluding the solvent, the same below), 100 parts by mass of an epoxy resin (BL1), and 4.0 parts by mass of a cationic polymerization initiator (C1) were diluted with methyl ethyl ketone to prepare a resin composition (1) having an active ingredient concentration of 40% by mass.

[0187] The resin composition (1) was applied to the release-treated surface of a release film (manufactured by Lintec, trade name: SP-PET752150), and the resulting coating was dried at 100° C. for 2 minutes to form a sheet-like adhesive having a thickness of 5 μm. The release-treated surface of another release film (manufactured by Lintec, trade name: SP-PET381031) was attached to the sheet-like adhesive to prepare a sheet-like adhesive (1) with a release film.

[0188] [Examples 2 to 8, Comparative Examples 1 to 2]

[0189] Sheet-like adhesives (2) to (10) with release films were prepared in the same manner as in Example 1 except that the components listed in Table 1 were used as the components constituting the sheet-like adhesive.

[0190] The following tests were conducted on the release film-attached sheet-like adhesives (1) to (10) obtained in Examples 1 to 8 and Comparative Examples 1 and 2. The results are shown in Table 1.

[0191] [Storage shear modulus (G') of cured sheet adhesive]

[0192] The storage shear modulus (G') of the cured product of the sheet-like adhesive was measured by a torsional shear method using a viscoelasticity measuring apparatus (manufactured by Anton Paar, product name: MCR302) in accordance with JIS K7244-6.

[0193] The details of the assay method are as follows.

[0194] (Preparation of Measurement Samples)

[0195] After peeling off the release sheet from the sheet adhesive with release film obtained in the examples and comparative examples, the sheet adhesive was overlapped to obtain a laminate with a thickness of 0.5 mm. The laminate of the obtained sheet adhesive was irradiated with UV to cure the laminate composed of the sheet adhesive. After UV irradiation, the laminate was left to stand at 23° C. for 24 hours to obtain a cured product of the sheet adhesive (laminate).

[0196] It should be noted that UV irradiation was performed under the following irradiation conditions: a high-pressure mercury lamp manufactured by Eye Graphics was used, and the illuminance when measured was 200 mW / cm2 at a temperature of 23°C and a wavelength of 365 nm. 2 , the cumulative light intensity is 1000mJ / cm 2 The light meter used was "UVPF-A1" manufactured by Eye Graphics.

[0197] The cured product of the sheet-like adhesive (laminated body) was punched out into a cylindrical body having a diameter of 8 mm (height of 0.5 mm), and this was used as a measurement sample.

[0198] (Determination of storage shear modulus (G'))

[0199] The storage shear modulus (G') was measured using the obtained test sample at a frequency of 1 Hz, a test start temperature of -20°C, a test end temperature of +150°C, and a heating rate of 3°C / min. The values ​​at 0°C and 100°C are shown in Table 1.

[0200] In addition, since the storage shear modulus of the cured products of the sheet-like adhesives (laminated bodies) obtained in Comparative Examples 1 and 2 was too high, slippage occurred in the above-mentioned torsional shear method and measurement could not be performed.

[0201] Therefore, the storage modulus (E') of the cured products of the sheet-like adhesives (laminated bodies) obtained in Comparative Examples 1 and 2 was measured using a dynamic viscoelasticity measuring apparatus (DMAQ800 manufactured by TA Instruments) in accordance with JIS K 7244-4 (1999), and the storage shear modulus (G') was calculated from the approximate formula "E'=3G'".

[0202] The details of the method for measuring the storage modulus (E') are as follows.

[0203] (Preparation of Measurement Samples)

[0204] After obtaining a cured product of the sheet-like adhesive (laminated body) by the same method as described above, the cured product of the sheet-like adhesive (laminated body) was processed into a size of 30 mm in length and 5 mm in width, and this was used as a measurement sample.

[0205] (Determination of storage modulus (E'))

[0206] The storage modulus (E') was measured using the obtained measurement sample under the conditions of a frequency of 1 Hz, a test start temperature of -20°C, a test end temperature of 150°C, and a temperature increase rate of 3°C / min.

[0207] [Reference Example 1]

[0208] The sheet-like adhesive obtained in Comparative Example 2 was irradiated with ultraviolet rays and then subjected to a heat treatment at 150° C. for 2 hours instead of being allowed to stand at 23° C. for 24 hours.

[0209] As a result, G'0 is 4000MPa and G' 100 is 500MPa, G'0 / G' 100 is 8.

[0210] [Table 1]

[0211]

[0212] The following can be seen from Table 1.

[0213] The sheet-like adhesives (1) to (8) obtained in Examples 1 to 8 contain epoxy resin (BL), G'0 / G' 100 The value of is less than 100.

[0214] Thus, the sheet-like adhesives (1) to (8) obtained in Examples 1 to 8 are sheet-like adhesives that can be sufficiently cured only by light irradiation.

[0215] On the other hand, for the sheet-like adhesives (9) and (10) obtained in Comparative Examples 1 and 2, G'0 / G' 100 The value of is very large.

[0216] By comparing Reference Example 1 and Comparative Example 2, it can be inferred that in Comparative Example 2, since no heating treatment was performed, the curing reaction was not sufficiently performed, and G' 100 The value of G'0 / G' in Comparative Example 2 is significantly reduced. 100 The value of becomes larger.

Claims

1. A photocurable sheet adhesive comprising the following components (A), (B) and (C), in, At least one of the epoxy resins constituting the component (B) is an epoxy resin having an oxyalkylene structure and providing a cured product having a glass transition temperature (Tg) of 25° C. or less, The content of the epoxy resin having an oxyalkylene structure and providing a cured product having a glass transition temperature (Tg) of 25° C. or less is 35 to 75% by mass based on the total mass of the photocurable sheet adhesive. (A) component: a binder resin component composed of one or more binder resins; (B) component: an epoxy curable component composed of one or more epoxy resins; (C) Component: photocationic polymerization initiator.

2. The photocurable sheet-like adhesive according to claim 1, wherein At least one type of binder resin constituting the component (A) is a phenoxy resin.

3. The photocurable sheet-like adhesive according to claim 1, wherein At least one type of binder resin constituting the component (A) is a polyvinyl acetal resin.

4. The photocurable sheet-like adhesive according to claim 1, wherein At least one of the epoxy resins constituting the component (B) is liquid at 23°C.

5. The photocurable sheet-like adhesive according to any one of claims 1 to 4, wherein The photocurable sheet adhesive was cured using a high pressure mercury lamp under the following conditions to obtain a cured product, and the storage shear modulus (G'0) at 0°C and the storage shear modulus (G' 100 ), the following formula (I) is fully satisfied: G'0 / G' 100 <100 (1) Curing conditions of light-curing sheet adhesive: Temperature: 23℃; Illuminance when measured at a wavelength of 365 nm: 200 mW / cm 2 ; The total amount of light measured at a wavelength of 365 nm is 1000 mJ / cm 2 .

6. Use of the photocurable sheet-like adhesive according to any one of claims 1 to 5 for producing an optical device.

Citation Information

Patent Citations

  • Thermosetting adhesive sheet, article and method for producing article

    JP2017110128A

  • Photocurable resin composition, sealing agent for organic el element, and organic el element

    JP2011225773A

  • Photocurable adhesive film for organic electronic device seal, organic electronic device, and method for sealing same

    US20140319497A1